London 2012 Paralympic swimming: passive drag and the classification system - Blauwet, C. A.; Benjamin-Laing, H.; Stomphorst, J.; Van de Vliet, P.; Pit-Grosheide, P.; Willick, S. E. (British Journal of Sports Medicine, 2013)
Background The key difference between the Olympic and Paralympic Games is the use of classification systems within Paralympic sports to provide a fair competition for athletes with a range of physical disabilities. In 2009, the International Paralympic Committee mandated the development of new, evidence-based classification systems. This study aims to assess objectively the swimming classification system by determining the relationship between passive drag and level of swimming-specific impairment, as defined by the current swimming class.